Global Economic Prospects 2004 : Realizing the Development Promise of the Doha Agenda - World Bank (Washington, DC, 2013)
The international community finds itself at a crossroads as it approaches the last quarter of 2003. Will the Doha Agenda regenerate the multilateral consensus that has been the hallmark of successive rounds of trade liberalization since 1947 and in doing so provide new impetus for global integration? Or will the Doha Agenda collapse in stalemate and perhaps be viewed as the moment when the international community retreated from multilateralism and opened the floodgates for less desirable bilateral and regional arrangements? The round has the opportunity to remove many of the inequities in the global trading system that put developing countries-and poor people in particular-at a disadvantage in their trade. Several issues under discussion are pivotal to development outcomes. They are the focus of this report: First, because most poor people live in rural areas, trade barriers in agriculture are among the most important to poverty reduction. Second, labor-intensive manufactures have been the most dynamic market segment for every major region, including Africa, yet many developing countries find that their exports meet obstacles in foreign markets-high tariffs, quotas, specific duties, and "antidevelopment" tariff structures that discourage adding value in poor countries. Third, in services, the potential for development-promoting reciprocal gains is especially high. Regulations in some developing countries still protect some inefficient state monopolies from competition-a drag on growth. (To be sure, proper regulation in some sectors must precede liberalization to avoid potential disruptions in socially important markets, such as finance or basic services.) Also, access for developing countries' services exports to industrial countries has yet to be fully bound in the General Agreement on Trade in Services (GATS) (World Bank 2001). Finally, national laws prevent greater labor mobility that would otherwise contribute to higher standards of living in both receiving and sending countries. Fourth, reducing the costs of trading by improving international transportation services, customs and ports, and logistics management- trade facilitation-requires substantial new investment, additional technical assistance, and coordinated multilateral efforts. Trade facilitation is fundamental to realizing the expanded trade promise of Doha, but the WTO agenda constitutes a small part of the challenge. Finally, the issue of special treatment for developing countries cuts across all of these policy domains and affects trade preferences and exemptions from WTO regulations. The pursuit of trade preferences and exemptions from multilateral rules have not always served developing countries particularly well, both because preferences have not proven reliable and because selective coverage has often left productivity-detracting trade barriers in place. The residual barriers sap growth in the protected economies and in developing-country trading partners that are denied access. Perhaps most important, the majority of the world's poor do not live in the least developed countries (LDCs). Trade preferences targeted at these countries do not benefit the three quarters of the world's poor that live on US$1 per day in other countries. In implementing new WTO rules, new accords will be most effective if they recognize differences among individual countries' capacity to undertake new, resource-intensive rules. These differences require a new approach to special and differential treatment.